2005
DOI: 10.1007/s11199-005-1192-9
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Self-Objectification in the Experience of Women with Eating Disorders

Abstract: Objectification theory has linked self-objectification to negative emotional experiences and disordered eating behavior in cultures that sexually objectify the female body. This link has not been empirically tested in a clinical sample of women with eating disorders. In the present effort, 209 women in residential treatment for eating disorders completed self-report measures of self-objectification, body shame, media influence, and drive for thinness on admission to treatment. Results demonstrated that the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
130
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 205 publications
(150 citation statements)
references
References 20 publications
9
130
1
3
Order By: Relevance
“…Body surveillance and body shame were not observed to be related to eating disordered attitudes, unlike what researchers have shown, which is that both are strong correlates of eating disordered behaviour (9,10).…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Body surveillance and body shame were not observed to be related to eating disordered attitudes, unlike what researchers have shown, which is that both are strong correlates of eating disordered behaviour (9,10).…”
Section: Discussioncontrasting
confidence: 92%
“…Therefore, distortion of the consciousness of the body, as an object, or negative affects toward the body could result in an abnormal eating attitude. Studies have shown a relationship between body image consciousness/awareness and the de- velopment of eating problems (7)(8)(9)(10)(11). Thus, objectification theory provides a useful conceptual framework for examining disordered eating attitudes (12).…”
Section: Introductionmentioning
confidence: 99%
“…Beberapa tahun terakhir ini, malu terkait tubuh kerap menjadi mediator di dalam berbagai studi teori selfobjectifation yang berupaya memahami gangguan makan. Sebagaimana penelitian yang dilakukan Calogero, Davis, dan Thompson (2005) menunjukkan malu terkait tubuh memediasi hubungan antara self-objectification dan keinginan untuk kurus.…”
Section: ; Bulimia Nervosa (Bn); Binge Eating Disorder (Bed); Dan Eatunclassified
“…These subjective experiences serve as the intermediate variables that link self-objectification to three specific mental health outcomes, which include depressed mood (Grabe, Hyde, & Lindberg, 2007;Tiggemann & Kuring, 2004), disordered eating (Calogero, Davis, & Thompson, 2005;Tylka & Hill, 2004;Tylka & Sabik, 2010), and sexual dysfunction Steer & Tiggemann, 2008). Thus, self-objectification indirectly contributes to greater depression, eating disorders, and sexual dysfunction in women by generating recurrent shame and anxiety, disrupting attention that could be directed toward pleasurable and rewarding activities, and reducing sensitivity to internal bodily cues.…”
Section: Consequences Of Self-objectificationmentioning
confidence: 99%